Phytochemical Investigations and In Vitro Bioactivity Screening on Melia azedarach L. Leaves Extract from Nepal. Issue 5 (30th March 2021) - Shrestha, Shyam Sharan; Ferrarese, Irene; Sut, Stefania; Zengin, Gokhan; Grana, Sara; Ak, Gunes; Pant, Deepak Raj; Dall'Acqua, Stefano; Rajbhandary, Sangeeta
Abstract: Melia azedarach is a common tree used in the traditional medicine of Nepal. In this work, leaves were considered as source of bioactive constituents and composition of methanol extract was evaluated and compared with starting plant material. Flavonoid glycosides and limonoids were identified and quantified by HPLC‐DAD‐MS n approaches in dried leaves and methanolic extract, while HPLC‐APCI‐MS n and GC/MS analysis were used to study phytosterol and lipid compositions. β ‐Sitosterol and rutin were the most abundant constituents. HPLC‐APCI‐MS n and HPLC‐DAD‐MS n analysis revealed high levels of phytosterols and flavonoids in methanolic extract accounting 9.6 and 7.5 % on the dried weight, respectively. On the other hand, HPLC/MS n data revealed that limonoid constituents were in minor amount in the extract <0.1 %, compared with leaves (0.7 %) indicating that degradation occurred during extraction or concentration procedures. The methanol extract was subjected to different bioassays, and antioxidant activity was evaluated. Limited inhibitory activity on acetyl and butyryl cholinesterase, as well as on amylase were detected. Moreover, tyrosinase inhibition was significant resulting in 131.57±0.51 mg kojic acid equivalents/g of dried methanol extract, suggesting possible use of this M. azedarach extract in skin hyperpigmentation conditions. Moderate cytotoxic activity, with IC50 of 26.4 μg/mL was observed against human ovarian cancer cell lines (2008 cells). Our findings indicate that the Nepalese M. azedarach leaves can be considered as valuable starting material for the extraction of phenolics and phytosterols, yielding extracts with possible cosmetic and pharmaceutical applications. Abstract :